2018
DOI: 10.1097/moh.0000000000000424
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in endothelial cell homeostasis and vascular disease

Abstract: Purpose of review Since the first discovery of microRNAs (miRNAs) in 1993, the involvement of miRNAs in different aspects of vascular disease has emerged as an important research field. In this review, we summarize the fundamental roles of miRNAs in controlling endothelial cell functions and their implication with several aspects of vascular dysfunction. Recent findings MiRNAs have been found to be critical modulators of endothelial homeostasis. The dysregulation of miRNAs has been linked to endothelial dysf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 130 publications
2
61
0
Order By: Relevance
“…Certain tissue-and "cell-specific" miRNAs have been clearly shown to be expressed in/and associated with cardiovascular settings and involve in maintaining vascular integrity [30]. Emerging evidence suggests that any changes or disruption into the arterial flow modulate the expression profiles of miRNAs of varied cells of luminal wall [31,32]. Studies have shown that several flow-sensitive miRNAs including miR-21, miR-23b, miR-92a, miR-19a, miR-143, miR-145, and miR-155, miR-205, miR-126 are directly or indirectly involved in the pathophysiological mechanism of atherosclerosis and therefore identified as mechano-miRs [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain tissue-and "cell-specific" miRNAs have been clearly shown to be expressed in/and associated with cardiovascular settings and involve in maintaining vascular integrity [30]. Emerging evidence suggests that any changes or disruption into the arterial flow modulate the expression profiles of miRNAs of varied cells of luminal wall [31,32]. Studies have shown that several flow-sensitive miRNAs including miR-21, miR-23b, miR-92a, miR-19a, miR-143, miR-145, and miR-155, miR-205, miR-126 are directly or indirectly involved in the pathophysiological mechanism of atherosclerosis and therefore identified as mechano-miRs [31].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers also tried to identify the role of miR-21 in AMI patients [43] but also addressed the limitation of its "cardiac specificity", as miR-21 is involved in multiple organs. This issue can certainly be overcome by using it in combination with other miRNA signatures as diagnostic markers as shown by other studies [32,44].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some mediators, such as miRNAs, are described to have a critical role in (patho)physiological processes, including atherosclerosis [70][71][72]. In particular, miR-126 exerts an atheroprotective effect [72,73] due to its role in restoring endothelium homeostasis [74].…”
Section: The Physio-pathological Role Of Hif In Agingmentioning
confidence: 99%
“…MicroRNAs (miRs) are post‐transcriptional regulators of gene expression that have been implicated as a novel class of molecules important in maintaining arterial health and mediating cardiovascular responses to exercise (Bartel, (2018); Donaldson, Lao, & Zeng, 2018; Fernández‐Hernando & Suárez, 2018; Lee & Chiu, 2019; Nanoudis, Pikilidou, Yavropoulou, & Zebekakis, 2017; Sapp, Shill, Roth, & Hagberg, 2017; Sapp & Hagberg, 2019). Circulating miRs (ci‐miRs) released from cells into the bloodstream are proposed as novel biomarkers and mediators of cardiovascular exercise responses, as well as CVD (Johnson, 2019; Njock & Fish, 2017; Sapp & Hagberg, 2019; Sapp et al., 2017,).…”
Section: Introductionmentioning
confidence: 99%